2014
DOI: 10.1371/journal.pone.0088044
|View full text |Cite
|
Sign up to set email alerts
|

Crossed Cerebellar Diaschisis in Acute Isolated Thalamic Infarction Detected by Dynamic Susceptibility Contrast Perfusion MRI

Abstract: PurposeCrossed cerebellar diaschisis (CCD) is a state of neural depression caused by loss of connections to injured neural structures remote from the cerebellum usually evaluated by positron emission tomography. Recently it has been shown that dynamic susceptibility contrast perfusion weighted MRI (PWI) may also be feasible to detect the phenomenon. In this study we aimed to assess the frequency of CCD on PWI in patients with acute thalamic infarction.MethodsFrom a MRI report database we identified patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…Although CCD has been shown to correlate with reduced fractional anisotropy along the corticospinal tract, results from one prior study correlating CCD from PET with fMRI were consistent with our results, finding not all subjects with CCD following chronic strokes have Wallerian degeneration [21]. While CCD has most commonly been associated with infarcts in areas involving the corticospinal tract, relationships between CCD and non-motor regions such as the thalamus [22], temporal association cortex and limbic system [23] have also been demonstrated [22]. In a study examining CCD with SPECT, Komaba Y, et al [24] identified only the postcentral and supramarginal gyrus as independent determinants of CCD after controlling for confounding effects.…”
Section: Discussionsupporting
confidence: 87%
“…Although CCD has been shown to correlate with reduced fractional anisotropy along the corticospinal tract, results from one prior study correlating CCD from PET with fMRI were consistent with our results, finding not all subjects with CCD following chronic strokes have Wallerian degeneration [21]. While CCD has most commonly been associated with infarcts in areas involving the corticospinal tract, relationships between CCD and non-motor regions such as the thalamus [22], temporal association cortex and limbic system [23] have also been demonstrated [22]. In a study examining CCD with SPECT, Komaba Y, et al [24] identified only the postcentral and supramarginal gyrus as independent determinants of CCD after controlling for confounding effects.…”
Section: Discussionsupporting
confidence: 87%
“…13,14,22,[25][26][27] The results of these studies, however, were predominantly obtained by analyses of small study populations (range: 18-113) 13,14,17,22,25,26,28 and/or by inclusion of various vascular territories 1,13,25,[27][28][29] and by inclusion of acute and chronic infarcts. 26,27 The strokes we investigated, however, were acute strokes restricted to the MCA territory to avoid a dispersion of the results by inclusion of different infarct stages and vascular territories.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we enrolled a large patient cohort which exceeded the size of study populations investigated in terms of CCD so far (mean: 51.1; range: 18-113). 13,14,17,22,25,26,28,52 Still, we cannot fully rule out the possibility of having underestimated the frequency of CCD as we counted only those cases as CCD positive, that show hemodynamic alterations suggestive of CCD in at least two perfusion parameter maps. However, artifacts on single perfusion maps can often be observed in CT imaging of the posterior fossa and this approach helped to limit the number of false-positive findings.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there are only a few reports on the application of DSC perfusion-weighted MRI (PWI) in TGA and all of these reported negative results [ 4 6 ]. However, meanwhile a substantial number of studies have been published addressing the detection of subtle perfusion abnormalities by use of PWI in different neurological disorders like migraine with aura [ 7 , 8 ], or crossed cerebellar diaschisis [ 9 , 10 ], an epiphenomenon in acute ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%